The socio-economic rank of parents and students’ academic and cognitive outcomes: Examining the physical, psychological and social mediators - Nja, Cecilia O.; Neji, Hope A.; Orim, Richard E.; Ukwetang, John O.; Ideba, Mary A.; Cornelius-Ukpepi, Bernedette; Ndifon, Rita A. (Frontiers in Education, 2022)
This study examined how the socioeconomic rank of parents correlates with students’ academic and cognitive outcomes of science students in senior secondary school. Its objective was to examine the bedrock of physical and psychosocial mediators that influence students’ learning and cognitive attitude. The sample comprised 548 science students drawn from 11 secondary schools in Calabar Municipality of Cross River State, Nigeria. A simple random sampling technique was used to select the sample from a population of 938 students. A cross-sectional observational type of survey design was used in this study. A self-reporting questionnaire labeled Socioeconomic Rank and Students Outcome Questionnaire (SERSOQ) was used for the study after validation and reliability. The results for reliability coefficients for SERSOQ range from 0.66 to 0.89 for Cronbach’s alpha and 0.72–0.81 for Kuder Richardson’s formula-20. Section “A” of SERSOQ was administered to the students in their schools by the research assistants, and students took section “B” home to their parents. Analysis of data collected was done using regression analysis, percentage, and mean. Results showed a great correlation between family income and academic achievement, cognitive attitude, and study habits. The study did not find a significant relationship between assignments with the variables under investigation. Importantly, the findings of this study found that parental control exhibited the greatest mediating function in providing family income impact on students’ cognitive attitude. Other mediators like students’ and peers’ educational ambitions and mother-child verbal relationships were discovered as potent mediators. Findings also showed a slight impact of family income on parent-child and mother-father relationships. Parental control consists of an influential setting that is outside the school environment yet mounting a very powerful effect on determining school outcomes in teenagers. In conclusion, a positive social environment is necessary for enhancing science students’ cognitive ability, academic achievement, and study habits as money is not everything. Some of the recommendations made were that there should be an educative environment at home. Educators should encourage parents to provide the necessary means of academic success, such as a source of light, stationery, books, separate study rooms, and homework facilities in their respective homes.